2023
DOI: 10.3847/2041-8213/acee80
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent Low-mass Galaxies Observed by JWST in the Epoch of Reionization

Viola Gelli,
Stefania Salvadori,
Andrea Ferrara
et al.

Abstract: The surprising JWST discovery of a quiescent, low-mass (M ⋆ = 108.7 M ⊙) galaxy at redshift z = 7.3 (JADES-GS-z7-01-QU) represents a unique opportunity to study the imprint of feedback processes on early galaxy evolution. We build a sample of 130 low-mass (M ⋆ ≲ 109.5 M ⊙) galaxies from the serra cosmological zoom-in simulations, which show a feedback-regulated, bursty star formation history (SFH). The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…However, in Gelli et al (2023), we showed that: (i) in order to reproduce the observed spectra of JADES-GS-z7-01-QU, an abrupt quenching of the simulated low-mass galaxy is required; and (ii) SNe alone cannot induce such an abrupt SF quenching in the low-mass galaxies identified in our cosmological simulations (Pallottini et al 2022). The same results have been later confirmed by Dome et al (2024) using the Illustris TNG, VELA, and FirstLight simulations.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, in Gelli et al (2023), we showed that: (i) in order to reproduce the observed spectra of JADES-GS-z7-01-QU, an abrupt quenching of the simulated low-mass galaxy is required; and (ii) SNe alone cannot induce such an abrupt SF quenching in the low-mass galaxies identified in our cosmological simulations (Pallottini et al 2022). The same results have been later confirmed by Dome et al (2024) using the Illustris TNG, VELA, and FirstLight simulations.…”
Section: Introductionsupporting
confidence: 75%
“…This finding lends further support to the previous studies based on cosmological simulations and quenching timescales reaching the same conclusion. In fact, not only does the quenching appear to be too swift to be produced by SNe (Gelli et al 2023;Dome et al 2024), but our model also convincingly shows that the SFR level sustained in the observed burst cannot produce enough energy to suppress SF.…”
Section: Interpreting Jades-gs-z7-01-qusupporting
confidence: 52%
See 1 more Smart Citation
“…The choice of feedback model has also been shown to impact the overall size-mass relation at low masses (e.g., Pillepich et al 2018), with the caveat that the sample is not separated into star-forming and quiescent populations. At higher redshifts, supernovae have been proposed as potential drivers of low-mass galaxy quenching, though they have been shown to not impart sufficient energy to halt star formation in the Looser et al (2024) or Strait et al (2023) high-redshift mini-quenched galaxy candidates (Gelli et al 2024(Gelli et al , 2023. Quenching via environmental interactions would result in minimal structural changes to the stellar light of low-mass galaxies, while stellar feedback quenching makes galaxies larger (Übler et al 2014).…”
Section: Structural Evolution At Low Massesmentioning
confidence: 99%
“…Hence, the dust produced by massive stars associated with the observed stellar population must have been efficiently evacuated (or destroyed) along with most of the gas by powerful galactic outflows driven by the radiation pressure produced by their compact (;100 pc), young (20-30 Myr) stellar component (Ferrara et al 2023;Fiore et al 2023;Ziparo et al 2023). Such feedback temporarily quenches star formation (Gelli et al 2023;Looser et al 2023) until the gas content of the galaxy is restored by efficient cosmological gas accretion, entailing a duty cycle of ;50-100 Myr.…”
Section: Introductionmentioning
confidence: 99%